Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fpsyg.2017.00833
|View full text |Cite
|
Sign up to set email alerts
|

Object Recognition in Mental Representations: Directions for Exploring Diagnostic Features through Visual Mental Imagery

Abstract: One of the fundamental goals of object recognition research is to understand how a cognitive representation produced from the output of filtered and transformed sensory information facilitates efficient viewer behavior. Given that mental imagery strongly resembles perceptual processes in both cortical regions and subjective visual qualities, it is reasonable to question whether mental imagery facilitates cognition in a manner similar to that of perceptual viewing: via the detection and recognition of distingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 108 publications
0
14
0
4
Order By: Relevance
“…Hence, this study has shown that the Spanish versions of the Psi-Q are an adequate measure for evaluating different sensorial modalities of imagery vividness and are valuable tools for the understanding of imagery as a psychological process or as a variable influencing other processes (Kharlas and Frewen, 2016;Denis and Poerio, 2017;Roldan, 2017;López-Pérez et al, 2018;Renner et al, 2019). The main limitation of this study was gender differences in the sample; notwithstanding, as the study was not designed to examine gender differences in this variable, this did not compromise the general objective of the study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, this study has shown that the Spanish versions of the Psi-Q are an adequate measure for evaluating different sensorial modalities of imagery vividness and are valuable tools for the understanding of imagery as a psychological process or as a variable influencing other processes (Kharlas and Frewen, 2016;Denis and Poerio, 2017;Roldan, 2017;López-Pérez et al, 2018;Renner et al, 2019). The main limitation of this study was gender differences in the sample; notwithstanding, as the study was not designed to examine gender differences in this variable, this did not compromise the general objective of the study.…”
Section: Discussionmentioning
confidence: 97%
“…The ongoing research in mental imagery highlights the need to design general measures of imagery vividness that include different sensorial modalities such as the Psi-Q. The review of applied research methods in mental imagery by Roldan (2017) has shown that the Psi-Q was a reliable, valid, and adequate measure for the study of mental imagery and as a first approximation to the analysis of other processes such as perception.…”
Section: Introductionmentioning
confidence: 99%
“…That could probably be attributed to one of the scenarios (VVIQ3 < 0.001) skewing the total. We have insufficient data to interpret this, but until further evidence our hesitant (since this is an established tool [60]) suggestion would be to either to use a different research tool to measure imagery capacity or to omit the 3rd scenario of the VVIQ in the context of BCI controlled robotic arm experiments.…”
Section: User Perception and Performance Assessment Our Resultsmentioning
confidence: 98%
“…The brain and eye analyze the visual perception of brightness, movement, shape, and color of objects [1,2] even the mental imagery of motion and static visual features [3,4]. The three basic color receptors of blue, green, and red have their own photo pigments that react to light to evoke receptor potentials in the visual pathway.…”
Section: Introductionmentioning
confidence: 99%